Biomolecules resveratrol + coenzyme Q10 recover the cell state of human mesenchymal stem cells after 1-methyl-4-phenylpyridinium-induced damage and improve proliferation and neural differentiation - Hernández-Pérez, Oscar R.; Juárez-Navarro, Karen J.; Diaz, Nestor F.; Padilla-Camberos, Eduardo; Beltran-Garcia, Miguel J.; Cardenas-Castrejon, Dalila; Corona-Perez, Héctor; Hernández-Jiménez, Claudia; Díaz-Martínez, Néstor E. (Frontiers in Neuroscience, 2022)
Neurodegenerative disorders are a critical affection with a high incidence around the world. Currently, there are no effective treatments to solve this problem. However, the application of mesenchymal stem cells (MSCs) and antioxidants in neurodegenerative diseases has shown to be a promising tool due to their multiple therapeutic effects. This work aimed to evaluate the effects of a combination of resveratrol (RSV) and coenzyme Q10 (CoQ10) on the proliferation and differentiation of MSC and the protector effects in induced damage. To characterize the MSCs, we performed flow cytometry, protocols of cellular differentiation, and immunocytochemistry analysis. The impact of RSV + CoQ10 in proliferation was evaluated by supplementing 2.5 and 10 μM of RSV + CoQ10 in a cellular kinetic for 14 days. Cell viability and lactate dehydrogenase levels (LDH) were also analyzed. The protective effect of RSV + CoQ10 was assessed by supplementing the treatment to damaged MSCs by 1-methyl-4-phenylpyridinium (MPP+); cellular viability, LDH, and reactive oxygen species (ROS) were evaluated.. MSCs expressed the surface markers CD44, CD73, CD90, and CD105 and showed multipotential ability. The combination of RSV + CoQ10 increased the proliferation potential and cell viability and decreased LDH levels. In addition, it reverted the effect of MPP+-induced damage in MSCs to enhance cell viability and decrease LDH and ROS. Finally, RSV + CoQ10 promoted the differentiation of neural progenitors. The combination of RSV + CoQ10 represents a potential treatment to improve MSCs capacities and protect against neurodegenerative damage.